Generation of Cressman Interpolated High-resolution Gauge-based Gridded Observations (CIHGGO) for climatic variables using in-situ data over Pakistan - Ahmad, Burhan; Ali Bukhari, Syed Ahsan; Babar Cheema, Sohail (European Journal of Scientific Exploration, 2019)
Scarcity of in-situ observations over an expanse of 881,913 km2 (including northern sides of high altitude regions) of Pakistan invites generation of gridded datasets at World Meteorological Organization’s (WMO’s) recommended spatial resolutions. Normally used for forecasts, projections and impacts assessments, gauge-based gridded datasets over particular regions have deficiencies either in spatial expanse of incorporated in-situ data or in robustness of long-term temporal scales over particular regions. This work has addressed these issues by incorporating quality controlled and strategically adopted 31 stations daily temperature and daily precipitation data in to an algorithm of designing a Cressman Interpolated High-resolution Gauge-based Gridded Observations (CIHGGO) at 0.45° (49.95 Km approximately) over a temporal scale of 39 years (1980-2018) for Pakistan region. The CIHGGO is available in NetCDF compression format for ease of use in decision support systems, research and applications.